IMPLEMENTASI PROGRAM BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DALAM PELAYANAN KESEHATAN DI UPTD PUSKESMAS III DINAS KESEHATAN KECAMATAN DENPASAR UTARA - Putu Suartama Suartama; I Wayan Astawa; I Kadek Dede Junaedy (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2025)
Indonesia has a large population with diverse geographical conditions, which poses challenges in providing equitable and affordable health services for the entire community. Although the BPJS Kesehatan program has been running for several years, the implementation of this program still faces various obstacles at the primary health service level such as Puskesmas. The importance of this study lies in efforts to improve the quality of health services provided by Puskesmas as first-level health facilities (FKTP). With the evaluation of the implementation of BPJS Kesehatan, it is hoped that this study can provide constructive recommendations for BPJS Kesehatan, the Health Office, and medical personnel in improving the quality of services. If the existing problems are not immediately resolved, then the main objective of BPJS Kesehatan in providing fair and equitable health services for all Indonesian people will not be achieved optimally. This study uses a qualitative research method with a descriptive approach that aims to understand social phenomena that occur in the natural environment in more depth, so that this study can produce something new where the results of this study found several important aspects related to the implementation of the BPJS Kesehatan program at Puskesmas III North Denpasar: (1) Ineffective Communication Between BPJS and Puskesmas, (2) Quality of Health Services, (3) Administrative Constraints. This study discusses the implementation of the BPJS Health Program in health services at the UPTD Puskesmas III, North Denpasar District Health Office. Based on the results of interviews, documentation, and observations that have been carried out, several main findings were obtained: (1) Communication Aspects in the Implementation of the BPJS Health Program, (2) Availability of Resources in BPJS Health Services, (3) Attitudes and Performance of BPJS Program Implementers, (4) Bureaucratic Structure and BPJS Regulations at the Puskesmas. The factors that are obstacles in the implementation of the Social Security Administering Body (BPJS) Health program in Health Services at the UPTD Puskesmas III, North Denpasar District Health Office are the still uneven socialization by BPJS Health to the general public, improvements in service quality that have not been significant, limited parking spaces and noise caused by the location of the UPTD Puskesmas which is right in a dense environment, and the lack of visitor queues when on certain days there are crowds of visits by the community to the UPTD Puskesmas III, North Denpasar.